Physiology and clinical applications of GIP - Shunsuke Yamane; Norio Harada; Nobuya Inagaki (Endocrine Journal)
Glucose-dependent insulinotropic polypeptide (GIP) is secreted by enteroendocrine K cells, primarily located in the upper small intestine, in response to food intake and plays a significant role in the postprandial regulation of nutrient metabolism. Although the importance of GIP in metabolic regulation has long been recognized, progress in developing GIP as a therapeutic target has been limited. However, the GIP/GIP receptor (GIPR) axis has garnered increasing attention in recent years. Emerging evidence suggests that dual GIP/GLP-1 receptor agonists and triple GIP/GLP-1/glucagon receptor agonists provide beneficial metabolic effects in individuals with type 2 diabetes and obesity. In this review, we outline the physiological roles of GIP, detailing the mechanisms of GIP secretion from K cells in response to macronutrients, its actions on key target organs involved in metabolic regulation, and ongoing developments in its therapeutic applications.